PEMBIAYAAN PRODUK CICILAN EMAS DALAM TINJAUAN HUKUM SYARIAH (Studi Kasus BMT NU Cabang Mayang) - Moch Rohiki Mahtum; sofiatus sobriyah sofiatus sobriyah; Khaerul Anam; Muhammad Aldi (KASBANA, 2025)
The development of the Islamic financial industry encourages microfinance institutions to continue to present innovative products, one of which is the Emas gold installment financing offered by KSPPS BMT NU East Java. This product is a sharia-based gold installment financing that aims to provide an alternative investment as well as a safe and affordable financing solution for the community. This study uses a qualitative approach with a descriptive method to examine how this product is implemented, including the contracts used and their advantages and challenges. The results of the study indicate that the implementation of contracts in Islamic Financial Institutions (LKS) in Indonesia has generally been carried out in accordance with sharia principles, but still faces significant challenges in terms of understanding and operational consistency. The main findings of this study highlight that the murabahah contract is most dominantly used because it is considered easier to implement and understand by customers and institutions. The main advantage of the implementation of the murabahah contract is to adjust to the financing needs of the community without violating the principle of the prohibition of usury. However, the most important challenge that must be understood in this context is the low level of sharia literacy among banking practitioners and customers, as well as the suboptimal internal supervision of sharia in maintaining the integrity of the contract. Keywords: Financing, Gold Installments, Sharia Law